Positive selection for loss of tetracycline resistance. - Bochner, B R (1980)
A simple technique has been devised that allows direct plate selection of tetracycline-sensitive clones from a predominantly tetracycline-resistant population. The technique is especially useful in genetic methodologies based on the use of tetracycline resistance transposons, such as Tn10. Potential uses of the method include selection of deletion mutants, fine-structure mapping, generalized mapping, construction of multiply marked strains, elimination of tetracycline resistance transposons and plasmids and cloning. The technique is based on our finding that tetracycline-resistant cells are hypersensitive to lipophilic chelating agents, such as fusaric acid. This finding supports the contention that certain metal ions critically facilitate tetracycline uptake and leads us to suggest possible molecular mechanisms for tetracycline resistance.